Factors Affecting Electronic Product Purchase Intention During Pandemic: The Moderating Effect of Gender and Occupation - Teguh Widodo; Putu Khrisna Mahadika (Universitas Negeri Semarang, 2023)
The research aims to analyze the electronic purchase intention, especially for laptops, which has grown more competitive, unpredictable, and dynamic during COVID-19 than ever before. Purchase intention has become a crucial concern for laptop marketers. Every marketer strives to update their strategy to compete in the market. In Indonesia, where the Covid-19 pandemic is raging, this study examined the influences of product features, brand image, and product price on consumers' intentions to acquire laptops. The survey was conducted with 363 respondents who responded to the structured questionnaire using a non-probability sampling technique. Data analysis using the PLS model was computed in this study using SmartPLS. The reliability and validity of the obtained data were examined using Cronbach's alpha, composite reliability, and average variance extracted. The hypotheses were examined using structural equation modeling (SEM). According to the study's findings, the price, brand image, and features of laptops all have a substantial impact on purchase intention. The influence of product features and brand image on laptop purchase intention is moderated by gender. However, occupation does not have an influence on how the effect modifies purchase intention. The study's findings will support laptop marketers in redesigning their segmentation, targeting, differentiation, and positioning strategies, as well as their pandemic and post-pandemic 4P marketing mix plans.